MoU signing ceremony and academic & research collaboration between Universiti Teknologi MARA and Mangayarkarasi College of Engineering, Madurai Tamilnadu, India / Nor Aziyah Bakhari, Marina Mokhtar and Suhaiza Hasan - Bakhari, Nor Aziyah; Mokhtar, Marina; Hasan, Suhaiza (UiTM Global @ Office of International Affairs, 2024)
Mangayarkarasi College of Engineering (MCE) in Madurai, Tamil Nadu, India, is under the patronage of Mangayarkarasi Education Trust, which has been in the field of education for the past seventy-five years in Madurai, the cultural capital of Tamil Nadu. This institution focuses on education in the fields of science, engineering, and technology and has nearly 15,000 students and 650 staff members dedicated to promoting quality education with a traditional touch that emphasises humanitarian service and the promotion of human values.